Application of response surface methodology for the optimization of polycyclic aromatic hydrocarbons degradation from potable water using photo-Fenton oxidation process - Abd Manan T.S.B.; Khan T.; Sivapalan S.; Jusoh H.; Sapari N.; Sarwono A.; Ramli R.M.; Harimurti S.; Beddu S.; Sadon S.N.; Kamal N.L.M.; Malakahmad A. (Elsevier B.V., 2023)
Aromatization; Developing countries; Gas chromatography; Hydrocarbons; Image processing; Iron compounds; Mass spectrometry; Mineral oils; Optimization; Organic carbon; Oxidation; Potable water; Solutions; Surface properties; Water pollution; Water treatment; Advanced Oxidation Processes; Central composite designs; Conventional water treatment; Gas chromatography-mass spectrometry; Photo-fenton oxidations; Photo-Fenton treatments; Polycyclic aromatic hydrocarbons (PAHS); Response surface methodology; Polycyclic aromatic hydrocarbons; drinking water; ferrous gluconate; ferrous sulfate; hydrogen peroxide; polycyclic aromatic hydrocarbon; aqueous solution; degradation; drinking water; gas chromatography; mass spectrometry; optimization; oxidation; PAH; response surface methodology; water treatment plant; aqueous solution; Article; biodegradation; chemical interaction; developing country; Malaysia; mass fragmentography; pH; photooxidation; priority journal; probability; reaction time; response surface method; total organic carbon; waste component removal; water contamination; water sampling; water treatment; Malaysia; Perak; West Malaysia